Influence of knowledge on Brazilian student's perception of life and clinical classes during COVID-19 - E Silva Ramos, Fernanda [UNESP]; Castro Oliveira, Laryssa [UNESP]; Mardegan Gonçalves, Diego [UNESP]; Rocha, Rafael [UNESP]; Bresciani, Eduardo [UNESP]; Fagundes, Ticiane Cestari [UNESP] (Wolters Kluwer, 2022)
BACKGROUND: The current pandemic associated with SARS-CoV-2 has negatively influenced several activities, including teaching in Operative Dentistry. The aim of this study was to evaluate the influence of knowledge in Operative Dentistry on undergraduate students' perception related to personal life and return to clinical practices classes during pandemic. MATERIALS AND METHODS: The present research was a cross-sectional, observational, and qualitative survey. The 16-item based questionnaire was sent to undergraduate students in 2020, which were divided into two groups, according to the Operative Dentistry knowledge: G1-not started clinical practice; G2-already started or completed clinical practice. Questions were focused on the impact of the pandemic in relation to their personal lives and return to clinical practice classes. Chi-square association test was performed using the SigmaPlot 12.0 software (P ≤ 0.05). RESULTS: The response rate was 55.5% for G1 and 44.4% for G2. Regarding the questions related to personal life, G1 demonstrated higher percentages of fear of contracting the virus during theoretical classes. Same observations were found when students answered about their fear of contracting coronavirus during the clinical practice classes. However, G2 presented the highest agreement responses for the preparedness feeling to return to theoretical classroom, clinical practice classes, and the possibility of applying online learning. CONCLUSIONS: In general, students' knowledge had little influence on perception of personal life. However, students who have more knowledge in operative dentistry presented more security about returning to clinical classes.
Keywords: Coronavirus; dental education; perception; students; teaching methods